The Influence of Parenting Patterns, Friends and Gadgets on Children's Emotional Development in Gugus Bintang Kejora South Banjarmasin - Marfu'ah, Marfu'ah; Suriansyah, Ahmad; Sakerani, Sakerani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to analyze the influence of parenting patterns, friends and gadgets on children's emotional development. The type of research used in this study is quantitative research that is associative causal. The population in this study were parents at Gugus Bintang Kejora Banjarmasin Selatan consisting of 167 students and a research sample of 118 respondents. The data analysis technique used multiple linear regression. The results of the study obtained (1) Parenting patterns affect children's emotional development (2) Friends affect children's emotional development (3) Gadgets affect children's emotional development (4) Parenting patterns, peers and gadgets simultaneously affect children's emotional development in the Gugus Bintang Kejora.